2019
DOI: 10.21037/atm.2019.08.21
|View full text |Cite
|
Sign up to set email alerts
|

From WOEST to AUGUSTUS: a review of safety and efficacy of triple versus dual antithrombotic regimens in patients with atrial fibrillation requiring percutaneous coronary intervention for acute coronary syndrome

Abstract: For patients with atrial fibrillation with concomitant acute coronary syndrome (ACS) requiring percutaneous coronary intervention (PCI), the increased risk of bleeding associated with the use triple therapy is well established. However, there is question whether it is a necessary risk for patients to prevent stroke and stent thrombosis. The purpose of this article is to highlight the findings of prior studies evaluating the comparative safety and efficacy of dual and triple antithrombotic regimens in the subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The recent AUGUSTUS study was designed for AF patients who had ACS or had undergone PCI and were taking a P 2 Y 12 inhibitor to receive apixaban or warfarin and aspirin or a matching placebo for 6 months ( 17 , 18 ). However, more than 90% of the individuals in this trial were treated with clopidogrel instead of more potent agents, such as ticagrelor.…”
Section: Introductionmentioning
confidence: 99%
“…The recent AUGUSTUS study was designed for AF patients who had ACS or had undergone PCI and were taking a P 2 Y 12 inhibitor to receive apixaban or warfarin and aspirin or a matching placebo for 6 months ( 17 , 18 ). However, more than 90% of the individuals in this trial were treated with clopidogrel instead of more potent agents, such as ticagrelor.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with non-valvular AF undergoing PCI, dual therapy (OAC plus a single antiplatelet) has consistently been associated with a lower risk of major haemorrhage compared with triple therapy (OAC and dual antiplatelet therapy) but a signal to early ischaemic risk is recognised [ 76 ]. The AUGUSTUS trial (antithrombotic therapy after acute coronary syndrome or PCI in atrial fibrillation) (discussed previously [ 56 ]) reported less bleeding with apixaban vs. vitamin K antagonist (VKA) and with placebo vs. aspirin at 6 months but the number of ischaemic events was numerically higher with placebo.…”
Section: Methodsmentioning
confidence: 99%
“…29 There were no statistically significant differences in ischemic events or risk of stent thrombosis between the various cohorts. 30 Other meta-analyses of the same trials have found similar results. 31…”
Section: Meta-analysesmentioning
confidence: 60%